The Implementation of Coaching and Mentoring in Enhancing Teacher Performance in Madrasah - Hizamuddin Syah; Badrul Mudarris (Journal of Educational Management Research, 2025)
Improving teacher performance is crucial for enhancing the quality of education in madrasahs. This study aims to explore the implementation of a coaching and mentoring model to improve teacher performance, with a focus on sustainable professional development. This research employs a qualitative design with a descriptive approach, utilising participatory observation, in-depth interviews, and documentation analysis to collect data. The results indicate that the integrated coaching-mentoring model, consisting of diagnostic, development, and reflection phases, has successfully improved teachers’ professional, pedagogical, and social competencies. However, challenges such as time constraints and inadequate mentor training hinder its full effectiveness. In conclusion, coaching and mentoring implemented at madrasah have contributed to creating a collaborative and reflective work culture, but improvements are needed in mentor training and enhancing teachers’ reflective capacities. This study offers new insights into the application of coaching and mentoring grounded in Islamic values in madrasah settings, providing a sustainable model for teacher development in Islamic educational institutions.